WNT5A Interacts With FZD5 and LRP5 to Regulate Proliferation and Self-Renewal of Endometrial Mesenchymal Stem-Like Cells - Li, Tianqi; Chan, Rachel W.S.; Lee, Cheuk-Lun; Chiu, Philip C.N.; Li, Raymond H.W.; Ng, Ernest H.Y.; Yeung, William S.B. (Frontiers in Cell and Developmental Biology, 2022)
Endometrial mesenchymal stem-like cells (eMSC) reside in the basal layer of the endometrium and are responsible for the cyclic regeneration during the reproductive lives of women. The myometrial cells act as a component of the niche and regulate the stem cell fate through activation of WNT/β-catenin signaling via WNT5A. Since the WNT5A-responsive mechanisms on eMSC are still uncertain, we hypothesize that the WNT ligand - WNT5A works to activate the WNT/β-catenin signaling through binding to Frizzled receptors (FZDs) and co-receptor low density lipoprotein receptor-related protein 5 (LRP5). Amongst the various receptors which have been reported to interact with WNT5A, we found FZD5 abundantly expressed by eMSC when compared to unfractionated stromal cells. Neutralizing the protein expression by using anti-FZD5 antibody suppressed the stimulatory effects on phenotypic expression and the clonogenicity of eMSC in a myometrial cells-eMSC co-culture system as well as in L-Wnt5a conditioned medium. Gene silencing of FZD5 not only reduced the binding of WNT5A to eMSC, but also decreased the TCF/LEF transcriptional activities and expression of active β-catenin. Inhibition of LRP co-receptors with recombinant Dickkopf-1 protein significantly reduced the binding affinity of eMSC to WNT5A as well as the proliferation and self-renewal activity. During postpartum remodeling in mouse endometrium, active β-catenin (ABC) was detected in label-retaining stromal cells (LRSCs) and these ABC+ LRSCs express FZD5 and LRP5, suggesting the activation of the WNT/β-catenin signaling. In conclusion, our findings demonstrate the interaction of WNT5A, FZD5 and LRP5 in regulating the proliferation and self-renewal of eMSC through the WNT/β-catenin signaling.